Objetos de aprendizagem para o ensino de língua portuguesa em repositórios brasileiros - Bezerra, Jéssica Tayrine Gomes de Melo (2018)
This thesis aims to analyze how repositories (LOR) and its learning objects (LO) collections can favor the teaching and learning of Portuguese language (PL) in the final years of Elementary School. As a theoretical basis for our research we mainly support the contributions of Wiley (2003), Polsani (2003) and Leffa (2006) on concepts and characteristics of learning objects repositories, in the discussions about literacy (SOARES, 1998; 2002; 2004), in the notion of multiliteracy (ROJO, 2012; 2013; NEW LONDON GROUP, 1996; KALANTZIS; COPE, 2006 [2000]) and in the perspective of the new literacies (LANKSHEAR; KNOBEL, 2006; 2007). In order to reach the proposed objective, we analyze characteristics, functionalities and collections of six repositories in the Brazilian context classified in three macrocategories: public repositories maintained by federal ministries at the international and national levels, public repositories maintained by private initiatives and state secretariats and repositories maintained by postgraduate laboratories. From the observation of the repositories, we selected a corpus of 17 learning objects in order to verify elements of pedagogical and human-machine interaction proposed in the Pedagogic Software Evaluation Protocol (PSEP) (ARAÚJO; FREITAS, 2017). In the analysis of the data, we verified that in the repositories (LOR) there are a significant number of 862 LO of different typologies destined to the teaching and learning of Portuguese language. In the selected corpus of 17 OA, we observed different levels of quality to potentialize the teaching and learning of the Portuguese language through Information and Communication Digital Technologies (ICDT) and some inconsistencies regarding didactic-pedagogic and ergonomic aspects. In relation to didactic-pedagogical criteria, we verified the predominance of the conception of language as expression of thought, the type of prescriptive teaching, the high granularity / reusability, the structuring of positive content, absence of aid systems and linguistic analysis as an objective learning. Regarding the ergonomic / human-machine interaction criteria, we found the predominance of high usability, partial accessibility, high interoperability, average interactivity and average availability of documentation and support material. In this way, we recognize the PSEP as a relevant mechanism for evaluating technical and pedagogical aspects of different LO formats. Finally, we consider that the learning objects (LO) are resources that support the process of teaching and learning Portuguese Language (PL) in the final years of elementary education through its multimodal and interactive elements, but its use must be combined with broader classroom discussions and practices which can enable new literacies and multiletrations, as well as enhancing literacy.